Accounting Opproaches to Investment forms in Islamic Banks and the Impact of the World Financial Crisis on It(An Applied Study on Iraqi Islamic Banck for Investment and Development –Mosul Branch ) (Al-Mansour Journal, 2022)
Witness the banking arena of local and regional development dramatically in the progress of operations of Islamic banking, whether in the form of the establishment of Islamic banks, new or turning conventional banks to Islamicbanks, or in the form of open Islamic branches of conventional banks, in addition to Islamic banks already exist, and in the international arena institutions are international financial operations to provide Islamic banking,has also been recently established Islamic Bank of Britain in London. Although this development in Islamic banking is still in front of the Islamic banks a lot of challenges and effort to the development of work systems and the use of modern technology, and development and innovation of financial instruments, local and international to meet the growing needs of clients andface the competition banking domestic and international markets. Islamic banks are different operations, all aimed to boost development in the community and the investment comes in the forefront of these operations. Investment and work legally acceptable as long as the methods and means are not contrary to the provisions of Islamic law. This means the abandon interestrate system currently in place in banks, non-Islamic, and to find a replacement on the basis of partnership between the capital and the factor that will invest the money and this is what distinguishes the Islamic economic system fromother systems, other economic, since the Islamic Investment ways and methods of distinct aims to achieve the income from it. The most prominent of these systems is the system of profit-sharing and speculative system and the system of participation as well as multiple other systems